Determinan Kemandirian Keuangan Daerah Pada Kabupaten/Kota Di Jawa Timur - Anggi Wahyu Puspita; Gideon Setyo Budiwitjaksono (Pusat Riset dan Inovasi Nasional, 2023)
The objective of this research is to determine the influence of general allocation funds, special allocation funds, and revenue sharing funds on the financial independence of districts/cities in East Java. The research adopts a quantitative approach with secondary data taken from the TKDD Realization Report of districts/cities in East Java from 2018 to 2022, available on the DJPK website. The sampling technique used is purposive sampling, resulting in 29 samples. The analysis employed is multiple linear analysis. The findings of the research indicate that, partially, general allocation funds and special allocation funds have an impact on the financial independence of the region, while revenue sharing funds do not affect the financial independence of the region